Content Classes Delivered in English at a Private School in Medellín– A Case Study - Blandón, Rubén Darío Cano (IJRDO- Journal of Educational Research, 2017)
This thesis examines the implementation of geography and history classes delivered inEnglish in a private school in Medellin-Colombia from three perspectives: the teachers’profile, their methodology, and the use of materials in light of Content-Based Instruction(CBI). The data was collected through surveys, class observations, and interviews. Theresults indicate that the content teachers lack training in teaching their classes through themedium of English; that there is no integration of content and language teaching, and thatthere is absence of collaborative work between the language teachers and the contentteachers. This research also concludes that it is fundamental to revisit the concepts ofbilingualism and bilingual education in the Colombian context.